Enabling grasp action : generalized quality evaluation of grasp stability via contact stiffness from contact mechanics insight - Dong, Huixu (2020)
Performing a grasp is a pivotal capability for a robotic gripper. We propose a new evaluation approach of the quality of grasping stability via constructing a model of grasping stiffness based on the theory of contact mechanics. First, the mathematical models are built to explore “soft contact” and the general grasp stiffness between a finger and an object. Next, the grasping stiffness matrix is constructed to reflect the normal, tangential and torsion stiffness coefficients. Finally, we design two grasping cases to verify the proposed measurement criterion of the quality of grasping stability by comparing different grasping configurations. Specifically, a standard grasping index is used and compared with the minimum eigenvalue index of the constructed grasping stiffness we built. The comparison result reveals a similar tendency between them for measuring the quality of grasping stability and thus, validates the proposed approach.